National Geographic Magazine [computer file] The 1970s (vol. 155, no. 4, April 1979) Jan. 1970-April 1973, May 1973-August 1976, September 1976-December 1979 (The Complete National Geographic : 110 years of National Geographic Magazine on CD-ROM, 1888)
Speak with Koko, an amazing gorilla that learned sign language. Travel to Ethiopia and unearth the remains of Lucy, one of humankind's oldest known ancestors. Join Thor Heyerdahl on a death-defying transatlantic sea voyage in a papyrus reed boat, the RA II. Study pollution, the scourge of the industrialized world, and learn the ways many more captivating moments from the 1970s.